CHILDREN SOCIAL ATTRIBUTION BASED ON GENDER PERSPECTIVE - Refika Mastanora; Rudi Pranata; Oktri Permata Lani (State Institute of Islamic Studies Batusangkar, 2021)
Social attribution can appear spontaneously or through long considerations and thinking process. Factors influencing attribution is the attribution style; planned and unplanned attribution. This kind of behavior can arise due to emotional factors. Meanwhile, children's social attributions arise because of stereotypes or labeling that have been attached to society, thus it has an impact on children's understanding of gender since they were born. The existence of social construction regarding gender roles cannot be separated from how the paradigm views the labeling of the characteristics of women and men is. In children, this social attribution usually occurs because of the stereotype of gender roles taught to children. This stereotype is a labeling that begins based on the perception or point of view of a person. While gender role stereotypes are part of the discussion about gender